Eksistensi Paralegal dalam Pemberian Bantuan Hukum bagi Masyarakat Miskin - Eka N.A.M. Sihombing (Universitas Medan Area, 2019)
The role of paralegals is needed to handle cases of non-litigation and litigation to fulfill the need for legal aid rights for the poor in facing the law, however, the provision of the role of paralegals in providing litigation legal assistance as stated in article 11 and article 12 Minister of Law and Human Rights of Republic of Indonesia number 1 of 2018 concerning paralegals in the provision of legal assistance based on the Supreme Court decision number 22 P / HUM / 2018 was declared contrary to the higher laws and regulations, namely Law Number 18 of 2003 concerning Advocates and hence not generally accepted. Thus, after the Supreme Court's ruling, paralegals can no longer provide legal litigation aid. Advocate are the only professions who are authorized to carry out legal aid in litigation and court